Historical Study On Air Sport In Nineveh Governorate from 1963 – 2003 - Ramadan, Mohammed (Journal of Physical Education, 2018)
Historical Study On Air Sport In Nineveh Governorate from 1963 – 2003The study aimed at shedding the light on the history of air sport in Nineveh governorate and recording it as an important part of the Sports history of Nineveh Governorate for the historical period from 1963 to 2003. In addition to that, the researcher aimed at documenting the names of players, trainers and administrators participating in international and local competitions. The researcher used the historical approach. The data was collected and discussed based on historical facts and references. Finally the researcher came up with a set of conclusions and recommendations.